HOMESCHOOLING SEBAGAI MODEL PENDIDIKAN PEMBEBASAN - Hariyanto, Erie (JURNAL KARSA (Terakreditasi No. 80/DIKTI/Kep/2012), 2012)
AbstractHomeschooling is a typeÂ  of optional education concept that is managed by parent. The instructional process must facilitate the development of studentâs unique potency. In the process of homeschooling, parents are free to select the curriculum, learning materials, and evaluation as they want. In Indonesia, it has a strong and legal basic and it appears as one of the potencies of eduactional model diversity that occurs in social life to realize an educationa liberation. Kata-kata kuncihomeschooling, pendidikan, pembebasan, anak didik